2021
DOI: 10.1039/d0nj05384h
|View full text |Cite
|
Sign up to set email alerts
|

Modulating photoelectrochemical water splitting performance by constructing a type-II heterojunction between g-C3N4 and BiOI

Abstract: g-C3N4/BiOI type-II heterojunction prepared by ultrasonically aided hydrothermal method exhibits high stability during PEC water splitting for up to 6000 s at 1.23 V vs. RHE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 64 publications
2
18
0
Order By: Relevance
“…4b). [30][31][32] As expected, g-C 3 N 4 /Q[6]-Co NPs possessed a maximum photoconversion efficiency (0.0242%), which was 12.6 times and 2.3 times higher than the values of bare g-C 3 N 4 (0.00193%) and Q [6]-Co NPs (0.0104%), respectively. The higher peak ABPE value indicated that the metal/semiconductor system could The band properties and semiconductor types were determined using the Mott-Schottky (M-S) diagrams based on the electrochemical impedance-potential measurements.…”
Section: Resultssupporting
confidence: 70%
“…4b). [30][31][32] As expected, g-C 3 N 4 /Q[6]-Co NPs possessed a maximum photoconversion efficiency (0.0242%), which was 12.6 times and 2.3 times higher than the values of bare g-C 3 N 4 (0.00193%) and Q [6]-Co NPs (0.0104%), respectively. The higher peak ABPE value indicated that the metal/semiconductor system could The band properties and semiconductor types were determined using the Mott-Schottky (M-S) diagrams based on the electrochemical impedance-potential measurements.…”
Section: Resultssupporting
confidence: 70%
“…A promising technology to utilize this solar energy is hydrogen fuel production through PEC water splitting. 69–71 Henri Becquerel first observed this phenomenon; he reported that sunlight acting on a silver chloride coated platinum electrode produced photocurrent and photovoltage in different electrolytes. The photochemical reaction cannot be stimulated in pure water as it only absorbs the infrared region, and the photon energy is low to stimulate a photochemical reaction.…”
Section: Types Of Water-splitting Technologiesmentioning
confidence: 99%
“…In order to compound the two particles in different morphologies, various compounding methods have been tried by previous authors. 22,23 According to the literature, g-C 3 N 4 /TiO 2 photocatalysts have been synthesized by hydrothermal reaction method, sol-gel method, and so template synthesis method, etc [24][25][26] .…”
Section: Introductionmentioning
confidence: 99%